Descriptive Study on Effects of Organizational Communication towards Organizational Citizenship Behaviour - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
Food tourism has become a familiar sector where several restaurants and food stores are focusing on maximizing the benefits of cuisine which benefits the individual producer or businessman in Punjab. Although food tourism has emerged lately and has become highly popular, there are certain hitches related to that of food tourism when it comes to Punjab. The present study is an attempt at discovering the problems and challenges associated with food tourism and to establish the perception of tourists regarding food as tourist attraction in Punjab. The present study is based on the collection of data through a self-structured questionnaire. The idea behind the research is to analyse the potential of food tourism in the states of Punjab. The study is intended to take place by the distribution of self-structured questionnaires in selected respondents in the states Amritsar, Jalandhar and Patiala and generalise the results to Punjab. The outcome of the questionnaire suggests that there is a positive correlation between food and tourism in Punjab. there is a significant relationship between food and tourist’s decision to visit Punjab and a positive relation between tourist’s perception and potential of food tourism in Punjab. In this examination the connection between authoritative duty and organization citizenship conduct is inspected. To this end, connection and mean and standart values have been done to uncover the impacts of organization correspondence on organization citizenship conduct. In this investigation, among the hierarchical correspondence measurements, just the component of correspondence with administrators is altogether related with alturism and city righteousness measurements of organization citizenship conduct.